"Quinoline Consists of 1H‐1, 2, 3‐Triazole Hybrids: Design, Synthesis and Anticancer Evaluation". Issue 48 (20th December 2019) - Venkata, Sivarami Reddy Gangireddy; C.Narkhede, Umesh; Jadhav, Vinod. D; Naidu, Challa Gangu; Addada, Ramakrishnam Raju; Pulya, Sravani; Ghosh, Balaram
Abstract: A series of novel 8‐bromo‐1 H ‐1, 2, 3‐triazol‐4‐yl‐2‐methylquinoline derivatives and their Suzuki coupling products were synthesized via Copper catalyzed azide‐alkyne cycloaddition (CuAAC) strategy followed by microwave assisted Suzuki coupling for the development of new series of anticancer agents. The invitro anticancer activity of the synthesized compounds were screened against human breast cancer (MDA‐MB‐231) and melanoma cell lines (B16F10). Among these, compounds 5 c (Azetidine), 5 e (Nitro benzoate), 5 f (fluorobenzyl)‐1 H ‐pyrazole), 5 g (Boc piperidine), 6 a (cyclo propyl), 6 c (5‐fluoro‐6‐methoxypyridin‐3‐yl)and 6 d (2‐methoxypyridin‐3‐yl) were showed anticancer activity ranging from 13.44 μM to 38.2 μM. The cellular toxicity of the novel compounds was also evaluated using normal human embryonic kidney (HEK) cell lines. Abstract : A series of 8‐bromo‐1 H ‐1, 2, 3‐triazol‐4‐yl‐2‐methylquinoline and their suzuki products were synthesized. The invitro anticancer activities were screened against MDA‐MB‐231 and B16F10 cell lines. Among these, 5 c (Azetidine), 5 e (Nitro benzoate), 5 f (fluorobenzyl)‐1 H ‐pyrazole), 5 g (Bocpiperidine), 6 a (cyclo propyl), 6 c (5‐fluoro‐6‐methoxypyridin‐3‐yl)and 6 d (2‐methoxypyridin‐3‐yl) were showed activity ranging from 13.44 μM to 38.2 μM. The cellular toxicity also evaluated using HEK cell line. Thus, these results deserve the need for further synthesis of similar libraries with other substituent's to ascertain the trend described in this work.